Α Smooth muscle actin positive stromal cells in gastric carcinoma. Issue 10 (1st October 2002) - Nakayama, H; Enzan, H; Miyazaki, E; Toi, M
Abstract : Aims: To investigate the distribution and roles of α smooth muscle actin (ASMA) positive stromal cells (ASMA+ cells), which belong to the myofibroblast group, within gastric carcinomas, with reference to three histological types (diffuse type, intestinal type, and solid type). Methods: In total, 74 surgically resected gastric carcinomas (24 diffuse type, 43 intestinal type, and seven solid type) were examined. ASMA positive and high molecular weight caldesmon (HCD) negative stromal cells were regarded as ASMA+ cells. The distribution of CD34 positive stromal cells (CD34+ cells) was also analysed immunohistochemically. Results: In the 24 diffuse-type gastric carcinomas, six of the 13 carcinomas invading the subserosa had ASMA+ cells in the tumour stroma, whereas all six diffuse-type gastric carcinomas confined to the submucosa and all five invading the muscularis propria had no ASMA+ cells in the tumour stroma. In the 43 intestinal-type gastric carcinomas, only five of the 21 carcinomas confined to the submucosa had ASMA+ cells in the tumour stroma, whereas 21 of the 22 intestinal-type gastric carcinomas invading the muscularis propria and the subserosa had ASMA+ cell bundles in the tumour stroma. The distribution of CD34+ cells in diffuse-type and intestinal-type gastric carcinomas was similar to that seen in a previously published series. All seven solid-type gastric carcinomas examined had ASMA+ cells but not CD34+ cells in the tumour stroma. No stromal cells double positive for ASMA and CD34 were detected within the diffuse-type tumours examined. Conclusions: These results suggest that ASMA expression in stromal cells is associated with tumour stroma formation of diffuse-type gastric carcinomas invading the subserosa, intestinal-type gastric carcinomas invading the muscularis propria and subserosa, and solid-type gastric carcinomas.